RULES OF VERBAL INTERACTION WITH CRIMINALS/EYEWITNESSES IN COURT TO FOSTER COOPERATION. - Pratibha Sinha (International Journal of Multidisciplinary Research and Studies, 2021)
The purpose of this chapter is to provide practical guidance on the protection of persons who come into contact with HROs in the context of human rights monitoring and fact-finding activities (hereinafter referred to as cooperating persons), and who may face threats or be subjected to reprisals as a result of that contact with HROs. interaction. The actions carried out by HROs when they are present in human rights field presences are the primary emphasis of this chapter as well as the Manual as a whole.